Role of Chemical Additives and their Rheological Properties in Enhanced Oil Recovery: A Review - Machale, J.; Majumder, S.; Ghosh, P.; Sen, Tushar (Freund Publishing House Ltd., 2019)
A significant amount of oil (i.e. 60–70%) remains trapped in reservoirs after the conventional primary and secondary methods of oil recovery. Enhanced oil recovery (EOR) methods are therefore necessary to recover the major fraction of unrecovered trapped oil from reservoirs to meet the present-day energy demands. The chemical EOR method is one of the promising methods where various chemical additives, such as alkalis, surfactants, polymer, and the combination of all alkali–surfactant–polymer (ASP) or surfactant–polymer (SP) solutions, are injected into the reservoir to improve the displacement and sweep efficiency. Every oil field has different conditions, which imposes new challenges toward alternative but more effective EOR techniques. Among such attractive alternative additives are polymeric surfactants, natural surfactants, nanoparticles, and self-assembled polymer systems for EOR. In this paper, water-soluble chemical additives such as alkalis, surfactants, polymer, and ASP or SP solution for chemical EOR are highlighted. This review also discusses the concepts and techniques related to the chemical methods of EOR, and highlights the rheological properties of the chemicals involved in the efficiency of EOR methods.